2021
DOI: 10.21203/rs.3.rs-911180/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combined effects of ENSO and PDO on Activity of Major Hurricanes in Eastern North Pacific

Abstract: Major hurricanes (MHs) in the eastern North Pacific (ENP) in 1970-2018 were clustered into 3 categories with different quantity, intensity, lifetime, translation speed, track and large-scale environmental fields. MHs in all three clusters are more active in the Pacific Decadal Oscillation (PDO) warm phase than cold phase period. There are two clusters that their relationship with El Niño Southern Oscillation (ENSO) were modulated by PDO. The first cluster generates and develops in the open ocean and has an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(33 reference statements)
1
0
0
Order By: Relevance
“…PDO, in particular, has been found to have an influence on the periodicity of TCs activity (Pazos & Mendoza, 2013) and landfalling events (Raga et al, 2013). Importantly, we found a positive correlation between MEI and PDO (Spearman's rho 0.678; p < 0.05) and other authors reported that a warm phase of PDO can strengthen an El Niño event (Huang et al, 2021; Wang & Liu, 2016). Moreover, interbasin teleconnections with the North Atlantic also modulates TC activity in the NEP.…”
Section: Discussionsupporting
confidence: 78%
“…PDO, in particular, has been found to have an influence on the periodicity of TCs activity (Pazos & Mendoza, 2013) and landfalling events (Raga et al, 2013). Importantly, we found a positive correlation between MEI and PDO (Spearman's rho 0.678; p < 0.05) and other authors reported that a warm phase of PDO can strengthen an El Niño event (Huang et al, 2021; Wang & Liu, 2016). Moreover, interbasin teleconnections with the North Atlantic also modulates TC activity in the NEP.…”
Section: Discussionsupporting
confidence: 78%